Hubungan Berat Badan dan Tinggi Badan Dengan Kecepatan Renang Gaya Bebas 50 Meter Pada Atlet Renang Noren Tirta Buana (NTB) - hendra hendra; Muhammad Suhdy; Muhammad Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between body weight and height with the speed of 50-meter freestyle swimming in Noren Tirta Buana (NTB) swimming athletes. The research method used in this study is the correlation method with data collection techniques using tests and measurements. The population and sample in this study were athletes Noren Tirta Buana (NTB) with a total sampling technique so that the sample was 15 people. The results of this study show that there is a significant relationship between body weight and swimming speed in the 50-meter crawl style for athletes Noren Tirta Buanaâ€; there is an important relationship between body height and swimming speed in the 50-meter crawl style for athletes Noren Tirta Buanaâ€; there is a significant relationship between body weight and size on the swimming speed of the 50-meter crawl style in female athletes 50 meters in athlete Noren Tirta Buana. In conclusion, there is a significant relationship between body weight and height in freestyle swimming speed in Noren Tirta Buana (NTB) swimming athletes. Keywords: Height, Swimming, Weight,